2014
DOI: 10.2337/db14-1220
|View full text |Cite
|
Sign up to set email alerts
|

Imeglimin Normalizes Glucose Tolerance and Insulin Sensitivity and Improves Mitochondrial Function in Liver of a High-Fat, High-Sucrose Diet Mice Model

Abstract: Imeglimin is the first in a new class of oral glucose-lowering agents currently in phase 2b development. Although imeglimin improves insulin sensitivity in humans, the molecular mechanisms are unknown. This study used a model of 16-week high-fat, high-sucrose diet (HFHSD) mice to characterize its antidiabetic effects. Six-week imeglimin treatment significantly decreased glycemia, restored normal glucose tolerance, and improved insulin sensitivity without modifying organs, body weights, and food intake. This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 32 publications
8
153
0
11
Order By: Relevance
“…Of note, our experimental design using succinate to fuel mitochondria in the presence of Rotenone specifically detected ROS production at mitochondrial Complex III (cytochrome C reductase). Based on recent studies, an additional contribution of ROS generation by reverse electron flow at Complex I (NADH‐dehydrogenase) is also feasible, as demonstrated in skeletal muscle (Brand, in press) and liver (Vial et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our experimental design using succinate to fuel mitochondria in the presence of Rotenone specifically detected ROS production at mitochondrial Complex III (cytochrome C reductase). Based on recent studies, an additional contribution of ROS generation by reverse electron flow at Complex I (NADH‐dehydrogenase) is also feasible, as demonstrated in skeletal muscle (Brand, in press) and liver (Vial et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were killed 15 min after injection, and gastrocnemius muscle and liver were rapidly removed and frozen. Protein kinase B (PKB) phosphorylation level, as an indicator of insulin pathway activation, was determined by western blotting (Vial et al 2015). Tissues were lysed in PBS buffer containing 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS supplemented with 5 mM EDTA, 1 mM Na 3 VO 4 , 20 mM NaF, 1 mM DTT and protease inhibitors cocktail (Sigma P2714, Saint Quentin Fallavier, France).…”
Section: Insulin Load Test and Analysis Of Insulin Signalling In Tissuesmentioning
confidence: 99%
“…S2 A-D). Of note, previous evidences have demonstrated that prolonged HFD feeding intake is able to promote insulin resistance and glucose intolerance (23)(24)(25). When obesity aspects were investigated, phenotypes of obesity and lipid accumulation in liver were significantly observed in HFD-fed WT mice compared with HFD-treated iRhom2 KO mice ( Fig.…”
Section: Irhom2 Deletion Protects Against High Fat Diet-induced Obesimentioning
confidence: 79%